MEDIA PEMBELAJARAN INTERAKTIF SEPARO UNTUK PELAJARAN PECAHAN DI SEKOLAH DASAR - Indah Nanindia Restiani; Ida Putriani; Desy Anindia (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2022)
One of the disadvantages of mathematical learning media in elementary school (elementary school) is that the media has not used interactive media. So the purpose of this study was to determine the feasibility and level of teacher legibility of SEPARO interactive learning media on fractional material for learning mathematics in elementary schools. The research method used is Research and Development (R&D) by Borg and Gall which is limited to seven steps. The approach used is qualitative and quantitative, in the form of a description of the product under study and the data obtained in the form of numerical data. SEPARO interactive learning media is designed using the Kodular application. To determine the feasibility of the product, validation was carried out to 3 validators, obtained an average value percentage of 90.61% by material experts in the very appropriate category, 84.57% by media experts in the appropriate category and 86.67% by linguists in the appropriate category. The results of the teacher test obtained an average percentage of 93.80% in the very feasible category, and the results of the student readability test obtained an average percentage of 94% in the very feasible category.